A Historical Study of the Arabic Language According to Islamic Scholars and Orientalists - Fauziyah, Nur Lailatul; Sahidah, Novita; Muntaha, Zahrotul Husnal (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Arabic is one of the oldest languages in the world. Over time, it has undergone significant transformation from the pre-Islamic (Jahiliyyah) period to the classical era. Numerous scholars have studied the history of the Arabic language, resulting in differing opinions. This study explores the historical development of Arabic by focusing on the views of both Islamic scholars and Orientalists, including As-Suyuthi, Abu Ali al-Faris, Ibn Jinni, Carl Brockelmann, P. H. Kitty, and Ernest Renan. The research employs a qualitative method by analyzing historical sources, including the perspectives of Islamic scholars and Orientalists. The objective of this study is to identify the factors influencing the historical development of the Arabic language.The findings indicate that the evolution of Arabic has been influenced by various factors, including religion, society, and culture.